Targeting fucosyltransferase FUT8 as a prospective therapeutic approach for DLBCL - Hao Xu; Qi Li; Yuchen Zhang; Chuan He; Xinyun Zhang; Zhiming Wang; Meifang Zhao; Yali Chai; Wenzhuo Zhuang; Bingzong Li (Oncogenesis)
Abstract Diffuse large B-cell lymphoma (DLBCL) is characterized by its aggressive nature and resistance to standard chemotherapy, necessitating the development of new therapeutic approaches. The emergence of natural products and their derivatives has notably influenced cancer treatment, making morusinol, a medicine-derived monomer, a promising candidate. Here, we showed that morusinol exerted antitumor effects on DLBCL in vitro by inducing apoptosis and cell cycle arrest. Impressively, morusinol treatment exhibited potent tumor growth inhibition in vivo, proving both well-tolerated and safe in mouse models. Moreover, our investigation identified FUT8, a fucosyltransferase, as a potential target for morusinol. FUT8’s role as an oncogene in DLBCL and its correlation with poor survival further underscored its significance. Furthermore, our screening efforts involving clinical and preclinical drugs unveiled a compelling synergistic effect between chidamide and morusinol. Additionally, morusinol’s ability to hinder M2-like polarization of tumor-associated macrophages suggested its potential in immune response modulation within DLBCL. Collectively, morusinol showcased substantial promise as an anti-tumor agent for potential clinical application in DLBCL management, potentially augmenting established therapeutic strategies. Moreover, our findings offered promising prospects for natural products to effectively leverage its therapeutic advantages. Working model: The role of Morusinol in treating DLBCL.